2005
DOI: 10.2220/biomedres.26.117
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid residues conferring the nucleotide binding properties of N-acetyl-D-glucosamine 2-epimerase (renin binding protein)

Abstract: Our recent studies have demonstrated that the middle domain of N-acetyl-D-glucosamine (GlcNAc) 2-epimerase participates in the specificity for and binding of nucleotides. To identify the residue conferring nucleotide binding, amino acid substitutions were introduced in the human and rat GlcNAc 2-epimerases. The mutational analyses indicate that residue 171 of GlcNAc 2-epimerase is critical for the nucleotide binding of GlcNAc 2-epimerase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In this article, we describe the cloning and expression of the CDS (bfce), and provide evidence that the recombinant protein (rBfCE) has CE activity. Many CDSs in various bacterial genomes, whose deduced amino acid sequences exhibit low identity to those of AGEs, have been annotated as hypothetical proteins of unknown function or putative AGEs, but few studies of functional AGEs (or reninbinding proteins) have been reported, and the enzymes have been found exclusively in mammals [11][12][13][14][15][16] and cyanobacteria. [17][18][19] Based on homology and phylogenetic analyses, we suggest that many CDSs in the bacterial genome sequences that share low but nonnegligible amino acid identity to AGE should be annotated as CE-like or putative CE proteins.…”
mentioning
confidence: 99%
“…In this article, we describe the cloning and expression of the CDS (bfce), and provide evidence that the recombinant protein (rBfCE) has CE activity. Many CDSs in various bacterial genomes, whose deduced amino acid sequences exhibit low identity to those of AGEs, have been annotated as hypothetical proteins of unknown function or putative AGEs, but few studies of functional AGEs (or reninbinding proteins) have been reported, and the enzymes have been found exclusively in mammals [11][12][13][14][15][16] and cyanobacteria. [17][18][19] Based on homology and phylogenetic analyses, we suggest that many CDSs in the bacterial genome sequences that share low but nonnegligible amino acid identity to AGE should be annotated as CE-like or putative CE proteins.…”
mentioning
confidence: 99%
“…In other mutational studies, an amino acid residue (Asn168) appeared to be crucial for AsNAL's increased k cat value [53] and Cys41 residue is important for hAGE stability [36]. Similarly, amino acid substitution introduced in human and rat AGE showed that residue 171 is critical for nucleotide binding [90]. Considering the structural and kinetic importance of amino acid residues, the current restrictive problems faced in maximizing NeuAc production can be resolved through enzyme modifications by increasing the substrate conversion rate of the AGE enzyme, reducing the enzyme cleavage activity of NALs, increasing the stability, and modifying the optimal reaction conditions (temperature, pH, metal ions, etc.)…”
Section: Protein Engineering Of Age and Nalmentioning
confidence: 93%
“…To date, two hypotheses have been put forward regarding the location of this site. One involves the H5/H6 loop and the other involves a glycine-rich fragment (residues 363-369 of AnaAGE) in the C-terminus (Lee, Chien et al, 2007;Liao et al, 2012;Sola-Carvajal et al, 2012;Takahashi et al, 2002Takahashi et al, , 2005. While the latter, which is based on sequence similarity to the motif of NTPases, is conserved across species, the evidence supporting the nonconserved H5/H6 loop is built on experiments using chimeric constructs, mutagenesis and ATP footprinting.…”
Section: Dimer Organization and Atp-binding Sitementioning
confidence: 99%